Notes for understanding the relationship between universities and political parties in Uruguayan history - Jung, María Eugenia; Markarian, Vania (CIAN-Revista de Historia de las Universidades, 2025)
The article analyzes the relationship between the University of the Republic, the only one of its kind between 1849 and 1984, and the Uruguayan political parties throughout the nineteenth and twentieth centuries. This relationship has been scarcely explored systematically in our historiography. Therefore, after briefly reviewing the development of the fields of studies on parties and the university in Uruguay, our journey begins with a review of the literature devoted to the incipient stages of institutional history, with the purpose of unraveling the attention paid to party politics. In the middle of the twentieth century, when the only university in the country became the object of heated debates, our gaze turns to a renewed documentary base to elucidate the weight of partisan identities in those conflicts. We continue the analysis in the latest decades, those following the democratic recovery of the 1980s, with some brushstrokes to understand the role of the parties in the new configuration of a higher education system with multiple institutions and demands coming from the political system and other social actors. We aspire to offer a narrative that perceives internal disputes as a substantial part of historical processes and not as contradictions to be overcome in order to achieve an ideal type of university supposedly consolidated in Latin America after the famous “Cordoba reform” of 1918.